Nilai Pendidikan dalam Kakawin Siwaratri Kalpa - I Wayan Mardana Putra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Kakawin has an important role for the Balinese Hindu community, not only as a part of the noble culture but also important in various ceremonial processions in Bali. In addition, as a form of cultural heritage, especially Hindu literature, of course kakawin itself has fair values in it, so that it can be used as a guide in living everyday life by Balinese people in particular. However, even though this kakawin is a Hindu literary work, the values in it can be applied universally by all people wherever they are. Value itself is something that includes wisdom, norms, manners in community life to create a civilization with good character. Kakawin Siwaratri Kalpa is important to be reviewed further because there are still many values that have not been reviewed in depth, so that their implementation during the Siwaratri celebration can be carried out as well as possible in a positive way. So thick are the values in Balinese literary heritage with Hinduism that the entire literary heritage must contain values that can be applied in everyday life. One of them is in Kakawin Siwaratri Kalpa. So the purpose of this research is to reveal and describe the values contained in Kakawin Siwaratri Kalpa. The results obtained that in Kakawin Siwaratri Kalpa there are values in it. These values are religious, logical, ethical, and aesthetic values. These values can be known, understood, and implemented for Hindus in particular and society in general in everyday life.